The Effect of Service Quality and Company Image on Customer Satisfaction of Ubasyada Cooperative in Ciputat Market, South Tangerang - Ariqa, Nida; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain how customer satisfaction at Ubasyada Cooperative in Pasar Ciputat, Tangerang Selatan, is influenced, both partially and simultaneously, by service quality and corporate image. Quantitative technique is the approach employed. Customers of Ubasyada Cooperative in Pasar Ciputat Tangerang Selatan made up the study's population. Probability sampling, which makes use of the Slovin formula, was the sample strategy employed. There were 97 responders in the research sample. Based on the study's findings, it can be said that customer satisfaction is positively and significantly impacted by service quality, as evidenced by the T_count value> T_table or (13.300> 1.986) with a significance value of 0.000 <0.05. Customer satisfaction is positively impacted by corporate image, as seen by the value of T_count > T_table, or (12.093 > 1.986), with a significance level of 0.000 < 0.05. Customer satisfaction is positively and significantly impacted by service quality and corporate image, as evidenced by the values of F_count > F_table or (99.944 > 3.090) with a significance level of 0.000 < 0.05. The regression effect of service quality and company image on customer satisfaction is Y = 8.282 + 0.322 X1 + 0.482 X2.